Link as a plan strategy From architecture to landscape - Gasparini, Christian (Urban, 2016)
Introduction Today architecture is, more then ever, an architecture of relationships instead of being an architecture of objects, of dynamic relational spaces instead of static scenes. The environmental emergencies of our times and the vanishing of the traditional urban forms in Europe as much as in other continents, make the meaning of this assumption wider and more true in regard to both the ‘natural’ territory and the anthropized territory. Architecture of relationships means the need to design the spatial and physical-perceptive connections between land and building, inside and outside, public and private uses, open and covered, natural and artificial, in an organic way and to give to these connection the value of primary meaning of the project itself. “Contemporary architecture is always more often a project of geography, a topographic project that directly links with the orographic and hydrographical characteristics of the site; it is always more often an interstice project, an agreement and a link between different morphological (urban or territorial) contests, often it is a relational project between layers that are under or over imposed to the country level, able to create strong relationship with the land layers and sub-layers in a vertical section.’ (Bocchi, 2009) Keywords Structure; identity; movement; connection; net